On prisoner's dilemmas and gilded cages: The economics of heritage preservation - Gabriel Ahlfeldt; Kristoffer Möller; Sevrin Waights; Nicolai Wendland (European Regional Science Association (ERSA), 2012)
Assuming that owners are fully compensated for the costs and benefits through the prices they pay for properties, we investigate the effects conservation areas have on value in England in a spatial hedonic analysis of property prices. Controlling for a particularly rich set of property and location attributes as well as unobserved spatiotemporal heterogeneity, our conditional estimates indicate a premium of about 8.5% for otherwise comparable properties located inside a conservation area. We detect heritage externality effect, which accounts for up to 4% of the value of properties located just outside conservation areas and becomes statistically indistinguishable from zero after about 500m. Within conservation areas, moving into the centre where heritage density is highest increases the premium by up to 100% compared to a location at the edge the conservation area boundary. The results from a spatiotemporal analysis indicate that the premium attached to a location inside as well as near to a conservation areas has significantly increased over time, but that the formal act of designation does not exhibit a statistically significant impact on property prices inside a conservation area. Joint with a moderate, but significant and decline in relative prices just outside the boundaries, the pattern of results does not support the presence of a supply driven increase in prices.
Keywords: 330